Analyse Applied Linguistics Research Trends in Google Scholar Using A Bibliometric Approach with VOSviewer - Hizbullah, Imam; Fauzi, Ach; Antarsyach, Anelka Almayda; Fathurrahman, Muhammad Albie (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
This study aims to identify research trends in the field of applied linguistics through bibliometric analysis. This study provides a comprehensive overview of the direction, focus, and productivity of the latest research in applied linguistics. Data collection was conducted on 5 March 2025, utilising the Google Scholar database with the keyword "applied linguistics," which yielded up to 500 journal samples. Version 8 of the Publish or Perish (PoP) application was used to gather this metadata. Descriptive analysis was performed on the data obtained from PoP, considering journal ranking, researcher productivity, publisher name, and year of publication. PoP data was exported in RIS format and analysed with the VOSViewer (VV) program to generate an accurate research progress map. The study's findings indicate a decline in the number of publications between 2019 and 2024, with a peak of 186 articles published in 2019. Jean-Marc Dewaele is the most prolific researcher, having published a total of 10 articles. The visualisation of the research progress map in applied linguistics reveals four main clusters: Cluster 1 includes 16 themes, Cluster 2 comprises 14 topics, Cluster 3 covers 11 topics, and Cluster 4 consists of 10 topics. These findings offer a clear overview of the recent developments and research focus in applied linguistics.